A Study of the Ornamental Fish Breeders in India for Analysing the Constraints in Enhancing Production - Sekharan, Mini; De, Soumya Subhra (Indian Journal of Marketing, 2010)
The supply chain of exotic ornamental fish for domestic marketing includes breeders at the first step followed by wholesalers, retailers and consumer/hobbyist where as the chain for export marketing includes breeders, suppliers, exporters and consumers/hobbyist abroad. The trend towards traceability, certification and improved farm management is driving responsibilities down the market chain to the breeders/breeding sector. Tomey (1997) pointed out that, with regards to recent developments in European legislation, tracking i.e. following a shipment from point of export to import and tracing i.e. the ability to follow the consignment all the way back to its original source, for example, a particular breeder or farm for health and welfare for all items are becoming a basic issue. Ornamental fish breeding/production has evolved from a pursuit into a sustainable livelihood alternative, comparable to agriculture or other activities of fisheries in India. Of late, this sector has been accorded wide recognition as a potent instrument for providing employment opportunities, slowing urban migrations, alleviating poverty, contributing to national income growth, and promoting equitable distribution of income and enhancing foreign exchange. In spite of the fact that India has conducive conditions for ornamental fish breeding, the production from the breeding sector is to the level of 100 Million fish per year. The ornamental fish export was to the tune of 535 Lakh (US $1.27 million) in 2008 (MPEDA, 2008). The demand for exotic fishes is high in the international ornamental fish markets such as USA, Europe, and UK. It is noted that in the domestic market for ornamental fishes, the supply from the breeding sector does not meet the domestic demand, which points at the fact that there remains no surplus stock for export. The domestic market for ornamental fishes in India is basically a sellers market and anything bred is devoured by the market without even considering the quality of it. For an industry to improve, the production level has to increase and the quality of the product also has to be enhanced.